A Game Theoretic Approach Against the Greedy Behavior in MAC IEEE 802.11 - El Houssaini, Mohammed-Alamine; Aaroud, Abdessadek; Hore, Ali El; Ben-Othman, Jalel (Ubiquitous Networking, 2017)
In recent years, mobile ad hoc networks are invading more and more our daily lives. Indeed, several persons are linked daily to ad hoc networks, which aim to exchange data via smartphones, computers, or tablets. A mobile ad hoc network is a group of mobile stations equipped with wireless transmitters/receivers without fixed infrastructure use or centralized administration. In this sense, the network can be seen as a random graph due to the motion of nodes. The change of the network topology based on the time when nodes move or adjust their transmission and reception parameters. The design of these networks is characterized by its vulnerability to denial of service (DOS) attacks such as the greedy behavior (MAC layer misbehavior). In this paper, we formalized the reaction against this malicious behavior of the MAC layer by game theory. We have developed a model in the extensive form of our reaction scheme and a resolution of the game by Kühn’s algorithm. A validation of results though the NS2 network simulator is then given to the end.